The effect psychobiotics on anxiety symptoms - Y. Denysov; G. Putyatin; S. Moroz; V. Semenikhina (European Psychiatry, 2023)
Introduction Psychobiotics are a group of probiotics that affect the central nervous system related functions and behaviors mediated by the gut-brain-axis via immune, humoral, neural, and metabolic pathways to improve not only the gastrointestinal function but also the antidepressant and anxiolytic capacity. Objectives An assessment of psychobiotic and anti-anxiety effects a probiotic supplement containing Lactobacillus Plantarum CECT7485 and Lactobacillus Brevis CECT7480 (PLANTARUM) in patients with anxiety undergoing treatment with selective serotonin reuptake inhibitors (SSRI) antidepressants. Methods Sixty patients with mixed anxiety and depressive disorder (according to ICD-10 diagnostic criteria F41.2) were included in an 8-week open label study. Thirty participants received either SSRI antidepressants with PLANTARUM at a dose of 1.0 × 109 CFU once per day and thirty patients received SSRI antidepressants only. The severity of anxiety symptoms was assessed using Hamilton Anxiety Rating Scale (HAM-A) and General Anxiety Disorder Scale (GAD-7). Results After 8 weeks intervention, a significant reduction of HAM-A total score (from 37,8±5,3 to 23,6±4,4) was detected in patients with anxiety who prescribed SSRI antidepressants and PLANTARUM (p˂0,05), compared with participants who didn’t receive probiotics (p>0,05). Also, a significant reduction of GAD-7 total score (from 21,7±3,3 to 12,5±2,4) was detected in patients with anxiety symptoms who received SSRI antidepressants and PLANTARUM (p˂0,01), compared with patients who didn’t intake probiotics (p>0,05). Conclusions The present data illustrated that probiotic supplement PLANTARUM is a feasible for adjunctive to SSRI antidepressants intervention for anxiety treatment. Disclosure of Interest None Declared